Lifestyle and risk factor management in people at high risk of cardiovascular disease. A report from the European Society of Cardiology European Action on Secondary and Primary Prevention by Intervention to Reduce Events (EUROASPIRE) IV cross-sectional survey in 14 European regions. (29th August 2020) - Kotseva, Kornelia; De Bacquer, Dirk; De Backer, Guy; Rydén, Lars; Jennings, Catriona; Gyberg, Viveca; Abreu, Ana; Aguiar, Carlos; Conde, Almudena C; Davletov, Kairat; Dilic, Mirza; Dolzhenko, Maryna; et al.
Abstract: Background: European Action on Secondary and Primary Prevention by Intervention to Reduce Events (EUROASPIRE) IV in primary care was a cross-sectional survey carried out by the European Society of Cardiology, EURObservational Research Programme in 2014–2015 in 71 centres from 14 European countries. The main objective was to determine whether the 2012 Joint European Societies' guidelines on cardiovascular disease (CVD) prevention in people at high CVD risk have been followed in clinical practice. Methods: Patients without a history of atherosclerotic disease started on either blood pressure and/or lipid and/or glucose-lowering treatments were identified and interviewed at least six months after the start of medication. Results: Medical notes of 6700 patients were reviewed, and 4579 patients (58.7% women; mean age 58.8 (standard deviation (SD) 11.3) years) interviewed (interview rate 68.3%). Overall, 16.6% were smokers, 39.9% were overweight (body mass index (BMI)≥25 and <30 kg/m 2 ), 43.5% obese (BMI ≥30 kg/m 2 ) and 63.9% centrally obese (waist circumference of ≥88 cm for women, ≥102 cm for men). The medical risk factor control was very poor, with less than half (42.8%) of the patients on blood pressure lowering medication reaching the target of <140/90 mm Hg (<140/80 mm Hg in people with self-reported diabetes). Among treated dyslipidaemic patients only 32.7% attained the low-density lipoprotein (LDL)-cholesterol target of <2.5 mmol/l. Among people treated for type 2 diabetes mellitus, 58.5% achieved the glycated haemoglobin (HbA1c) target of <7.0%. Conclusion: The EUROASPIRE IV survey shows that large proportions of patients at high CVD risk have unhealthy lifestyle habits and uncontrolled blood pressure, lipids and diabetes. The present data make it clear that more efforts must be taken to improve cardiovascular prevention in people at high CVD risk.